BASIC DIMENSIONS OF QUALITY HEALTHCARE IN ANCIENT SYSTEM OF INDIAN MEDICINE: A CUE FOR CURRENT PRACTICE - Bhoyar, Samir; Namburi, *U.R.Sekhar; Khode, Dr. Nakul; Jadhav, Shubhangi Satish; Suryawanshi, Milind N (International Journal of Ayurveda and Pharma Research, 2016)
Health is one of the basic and important requirements of every individual in the world. The health and its care is a complex phenomenon which can be managed by self or by health care professionals as per the conditions. Now a day’s several healthcare institutions are budding up however it is not ensured that everybody will get the kind of treatment they require. The main reason for this situation is lack in the quality and ethics in healthcare management. Healthcare system needs highly qualified doctors, paramedical staff and medicines which are critical for producing effective management and helps in high-quality outcomes, otherwise poor-quality care adds significantly to the costs of patients and sometimes results in delay in recovery from the disease or lead to major loss. Hence it is one of the very strong issues in health management in the present materialistic world.Ayurveda is a very distinct Indian medical science and has some unique qualities in catering the health service and management for the needy, based on the Chatushpada (four pillars of treatment) theory. It consists of Bhishag (physician), Upastha (medical attendant), Rogi (patient) and Dravya (medicine). These four factors are mutually dependant on each other and its proper employment gives good outcome of Chikitsa (treatment). Each of the four factors possesses four qualities essential for a treatment to be successful. In absence of any one of these, the treatment may not be successful. However among these four pillars, physician has got prime importance since in any case treatment is not possible in his absence.